Twelve weeks of supervised exercise improves self-reported symptom burden and fatigue in chronic kidney disease: A secondary analysis of the 'ExTra CKD' trial - Wilkinson, Thomas J.; Watson, Emma L.; Gould, Douglas W.; Xenophontos, Soteris; Clarke, Amy L.; Vogt, Barbara P. [UNESP]; Viana, João L.; Smith, Alice C. (Oxford University Press (OUP), 2019)
Background Chronic kidney disease (CKD) patients experience a high symptom burden including fatigue, sleep difficulties, muscle weakness and pain. These symptoms reduce levels of physical function (PF) and activity, and contribute to poor health-related quality of life (HRQoL). Despite the gathering evidence of positive physiological changes following exercise in CKD, there is limited evidence on its effect on self-reported symptom burden, fatigue, HRQoL and physical activity. Methods Thirty-six patients [mean ± SD 61.6 ± 11.8 years, 22 (61%) females, estimated glomerular filtration rate: 25.5 ± 7.8 mL/min/1.73 m 2 ] not requiring renal replacement therapy underwent 12 weeks (3 times/week) of supervised aerobic exercise (AE), or a combination (CE) of AE plus resistance training. Outcomes included self-reported symptom burden, fatigue, HRQoL and physical activity. Results Exercise reduced the total number of symptoms reported by 17% and had favourable effects on fatigue in both groups. AE reduced the frequency of 'itching', 'impotence' and 'shortness of breath' symptoms, and the intrusiveness for symptoms of 'sleep disturbance', 'loss of muscular strength/power', 'muscle spasm/stiffness' and 'restless legs'. The addition of resistance exercise in the CE group saw a reduction in 'loss of muscular strength/power'. No changes were seen in subjective PF or physical activity levels. AE increased self-efficacy for physical activity. Conclusions Supervised exercise had favourable effects on symptom frequency and intrusiveness, including substantial improvements in fatigue. Although the intervention did not improve self-reported physical activity levels, AE increased patients' self-efficacy for physical activity. These favourable changes in self-reported outcomes support the important role of exercise in CKD.
Keywords: chronic kidney disease; exercise; fatigue symptoms; health-related quality of life